Revisões sistemáticas como fonte de evidências científicas em saúde - Martínez-Silveira, Martha Silvia (2015)
Martha Silvia Martínez-Silveira. Fundação Oswaldo Cruz. Instituto Gonçalo Moniz. Salvador, BA, Brasil.